Fabrication of Microhotplate by Selective Laser Sintering of Micropowder for Thermal Conductivity Measuring Sensors. (2015) - Oblov, Konstantin; Ivanova, Anastasia; Soloviev, Sergey; Samotaev, Nikolay; Vasiliev, Alexey; Sokolov, Andrey; Pisliakov, Alexandr
Abstract: The layout of experimental samples of microhotplate based on nanocomposite material consisting of ruthenium dioxide and borosilicate glass binder were formed by selective laser sintering method. The resulting structures were used as microhotplate to measure changes in thermal conductivity of gases. The comparison of power consumption of standard platinum wire coil element widely used in thermocatalytic (calorimetric) sensors and microhotplate produced by the new technology showed strong advantage of the latter one.